REVITALIZATION OF ACEH CUSTOMS IN FORMAL EDUCATIONAL INSTITUTIONS - Suyanta, Sri; M. Nur, Chairan (UIN Ar-Raniry, 2016)
The study aims to strengthen the role of school in transforming Aceh customs. Schools as an official formal education institution, dealing with two issues namely their feelings cannot be ignored between customs and culture is a case that should be maintained continuously, and schools have to collide with system reining the power of cruising and creativity of education institutions in developing the value of custom. In addition, schools have a desire to interpret Aceh customary by themselves. Those things are done in two issues; First, the lack of teacher understanding customs well and perfectly. Secondly, low supported funding supporting every work in revitalization of custom. The study found that revitalization and strategy in developing in formal schools are undergone by two ways; theory and practice. Theoretically, schoolsÃ‚Â include custom materials through several lessons. Then practically, schools encourage studentsÃ¢â‚¬â„¢ creativity in many ways, both in school activities internally and externally.